Hydrogeochemistry and groundwater quality evaluation along the groundwater flow path in unconfined aquifer in Hankendi Plain, Elazig, Turkey - Çetindag, B; Ünsal, N (Geological Soc India, 2004)
The study area is located to the west of Elazig, in southeastern Turkey. Hydrochemical evolution of the groundwater is related to the flow path of groundwater. The groundwater in the unconfined aquifer may be classified in terms of Ca-Mg-HCO3 hydrochemical facies characterised by shallow (young) waters which dominate the recharge areas during rapid flow conditions. Ionic concentrations, TDS, EC and water quality are related to groundwater residence time and groundwater types. The groundwaters in the plain are chemically potable and suitable for both domestic and agricultural purposes.
Keywords: hydrogeochemistry; unconfined aquifer; water quality; Elazig; Turkey